Identification and expression responses of TCP gene family in Opisthopappus taihangensis under abiotic stress - Gao, Ting; Zhou, Xiaojuan; Han, Mian; Shen, Yuexin; Zhang, Yimeng; Wu, Qi; Dan, Haoyuan; Wang, Tingyu; Ye, Hang; Liu, Li; Chai, Min; Wang, Yiling (Frontiers in Plant Science, 2025)
The TCP gene family plays pivotal roles in the development and abiotic stress responses of plants; however, no data has been provided for this gene family in Opisthopappus taihangensis. Based on O. taihangensis genome, 14 TCP genes were identified and divided into two classes (I and II). After tandem and segmental duplication/whole-genome duplication (WGD), more loss and less gain events of OtTCPs occurred, which might be related with the underwent purifying selection during the evolution. The conserved motifs and structures of OtTCP genes contained light response, growth and development, hormone response, and stress-related cis-acting elements. Different OtTCP genes, even duplicated gene pairs, could be expressed in different tissues, which implied that OtTCP genes had diverse function. Among OtTCPs, OtTCP4, 9 and 11 of CYC clade (Class II) presented a relative wide expression pattern with no or one intron. The three TCP genes could be regarded as important candidate factors for O. taihangensis in growth, development and stress response. These results provided some clues and references for the further in-depth exploration of O. taihangensis resistance mechanisms, as well as those of other unique eco-environment plants.